Escalating Indecision: Between Reification and Strategic Ambiguity - Denis, Jean-Louis; Dompierre, Geneviève; Langley, Ann; Rouleau, Linda (Organization Science, 2011)
This paper examines an organizational pathology that we label “escalating indecision”—where people find themselves driven to invest time and energy in activities and decision processes aimed at resolving an issue of common concern, but where closure appears elusive. The phenomenon is illustrated through a case history in which a strategic orientation decision involving the configuration of a group of large teaching hospitals was continually made, unmade, and remade, producing little concrete strategic action over many years before achieving more tangible moves toward implementation. The paper introduces the notion of a “network of indecision” in which participants have become sufficiently attached to a common project to continue working together to move it forward, but their divergent conceptions of what this involves prevent them from materializing it in a tangible form. The paper suggests that networks of indecision are dialectically constituted through a set of practices of reification and practices of strategic ambiguity. The phenomenon is strongly associated with pluralistic settings characterized by diffuse power and divergent interests, and its prevalence is likely to be greater in situations of reactive leadership, uncertain resource availabilities, and long time horizons.